Prediction of Outcome after Traumatic Brain Injury Using Clinical and Neuroimaging Variables - Lee, Seo-Young (Korean Neurological Association, 2012)
BACKGROUND AND PURPOSE: The functional outcome of traumatic brain injury (TBI) varies widely. The aim of this study was to identify the factors predicting outcome following TBI. METHODS: We prospectively enrolled acute TBI patients, and assessed them clinically and radiologically using brain magnetic resonance imaging (MRI). Functional outcome was measured using the Glasgow Outcome Scale (GOS) at 3 months after TBI. A GOS score of ≤4 was regarded as an unfavorable outcome. We performed multivariate analysis to investigate the association between clinicoradiological variables and outcome. RESULTS: Forty-two patients completed the clinical evaluation in the acute phase and outcome measurement at 3 months. Motorcycle accident was associated with unfavorable outcome [odds ratio (OR)=38.3, p=0.022]. If the patients were the victims of the accident, they were more likely to have an unfavorable outcome (OR=21.3, p=0.037). All seven patients with a low Glasgow Coma Scale (GCS) score (i.e., ≤8) at 24 or 48 h after TBI were also found to have an unfavorable outcome. The presence of diffuse axonal injury (DAI) was a significant predicting factor of an unfavorable outcome (OR=8.48, p=0.042). CONCLUSIONS: Motorcycle accident, being an accident victim, and a lower GCS score at 24 hours or more after the accident were found to be unfavorable prognostic variables. DAI was the only radiologic variable predicting an unfavorable outcome. Thus, it is important to identify DAI by applying MRI in the acute phase.